2019
DOI: 10.4062/biomolther.2018.136
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Mechanism on Acetylcholine-Induced Contraction of Bladder Smooth Muscle in the Streptozotocin-Induced Diabetic Rat

Abstract: Most diabetic patients experience diabetic mellitus (DM) urinary bladder dysfunction. A number of studies evaluate bladder smooth muscle contraction in DM. In this study, we evaluated the change of bladder smooth muscle contraction between normal rats and DM rats. Furthermore, we used pharmacological inhibitors to determine the differences in the signaling pathways between normal and DM rats. Rats in the DM group received an intraperitoneal injection of 65 mg/kg streptozotocin and measured blood glucose level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…These results were in line with what was reported in our previous study, where arginase activity was repressed and NO levels was upregulated in the brain of diabetic rats fed with ML/MS supplemented diets cotreated with ACA (Oboh et al, 2018), and was linked to the presence of phenolic acid and flavonoid in the studied plant materials ( Several lines of research have shown that inhibition of PDE-5 alone is not enough in the management of ED, not even to talk about the side effects exhibited by PDE-5 synthetic inhibitors (Adebayo, Oboh, & Ademosun, 2019;Ademiluyi et al, 2019). However, other enzymes such as AChE, ACE, MAO, and ADA, among others, which, if unchecked, could also wreak havoc toward sustaining ED, via the reduction of concentration of some vital biomolecules including NO, angiotensin-I, cGMP, and adenosine in the penile tissue (Adefegha, Oyeleye, Dada, et al, 2018;Jung, Jo, Kwon, & Jeong, 2014;Naylor, 1998;Phatarpekar, Wen, & Xia, 2010), most especially in diabetic subjects (Adebayo et al, 2019;Han et al, 2019;Yang et al, 2009). In addition to the aforementioned, adenosine acts as neuromodulator in the corpus cavenosum and forestall relaxation of smooth muscle in penile tissue (Phatarpekar et al, 2010;Sebastiao & Ribeiro, 2000), and its reduction could be brought by the unchecked increase of ADA activity by converting it down to inosine (Adefegha, Oyeleye, Dada, et al, 2018;Leal et al, 2016).…”
Section: Discussionsmentioning
confidence: 99%
“…These results were in line with what was reported in our previous study, where arginase activity was repressed and NO levels was upregulated in the brain of diabetic rats fed with ML/MS supplemented diets cotreated with ACA (Oboh et al, 2018), and was linked to the presence of phenolic acid and flavonoid in the studied plant materials ( Several lines of research have shown that inhibition of PDE-5 alone is not enough in the management of ED, not even to talk about the side effects exhibited by PDE-5 synthetic inhibitors (Adebayo, Oboh, & Ademosun, 2019;Ademiluyi et al, 2019). However, other enzymes such as AChE, ACE, MAO, and ADA, among others, which, if unchecked, could also wreak havoc toward sustaining ED, via the reduction of concentration of some vital biomolecules including NO, angiotensin-I, cGMP, and adenosine in the penile tissue (Adefegha, Oyeleye, Dada, et al, 2018;Jung, Jo, Kwon, & Jeong, 2014;Naylor, 1998;Phatarpekar, Wen, & Xia, 2010), most especially in diabetic subjects (Adebayo et al, 2019;Han et al, 2019;Yang et al, 2009). In addition to the aforementioned, adenosine acts as neuromodulator in the corpus cavenosum and forestall relaxation of smooth muscle in penile tissue (Phatarpekar et al, 2010;Sebastiao & Ribeiro, 2000), and its reduction could be brought by the unchecked increase of ADA activity by converting it down to inosine (Adefegha, Oyeleye, Dada, et al, 2018;Leal et al, 2016).…”
Section: Discussionsmentioning
confidence: 99%
“…Therefore, the blocking of Ca 2+ channels or the reduction of Ca 2+ release from intracellular storage will weaken the contraction of intestinal smooth muscle. ACh is one of the most important neurotransmitters in gastrointestinal tract, which can bind to muscarinic M receptor and involve the activation of PLC, leading to the generation of inositol-1, 4, 5trisphosphate (IP3), which induces Ca 2+ release and leads to small intestine contraction [29,30]. The experimental results showed that EWOV could signi cantly relax the contraction of ACh (10 − 5 M) induced jejunum smooth muscle in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The social significance of this scientific theme is determined by the fact that diabetic cystopathy is a specific complication of DM, which is found in 30-87% of patients [17,21,24,25,29,34,37,40] and affects both social and the economic status of patients [23,27,38,39,42], and DM tends to be widespread [1,4,7,16,35]. According to the International Diabetes Organization [30], the incidence of this disease increases at 50% every 10 years, and the total number of patients with DM will reach 642 million persons before 2040 [33,44].…”
mentioning
confidence: 99%